Pollution assessment and source analysis of heavy metals in agricultural soil around Zijiang River estuary - Wenhui Liu; Teng Ma; Junqi Li; Xiancang Wu; Haotian Yu (地质科技通报, 2021)
Zijiang River is the second largest tributary of Dongting Lake. The developed antimony (Sb) mine mining and smelting industry in the upper and middle reaches of Zijiang River bring serious heavy metal pollution risks to the lower reaches of Zijiang River and the Dongting Lake. Taking Zijiang river Estuary as the study area, 132 agriculture soil samples and 7 water samples of Zijiang River were collected, and then multi-methods of contamination assessment, spatial analysis and multivariate statistical analysis methods were comprehensively used to evaluate pollution status and sources of the heavy metal this site. The results showed that the average concentration of heavy metals in farmland soil in the study area was Zn>Cr>Ni>Pb>Cu>As>Sb>Cd, and the average concentration of heavy metals in upland fields was higher than that in paddy fields except for Pb. Sb, As and Cd were the main pollution elements. Besides, Sb reached the level of medium pollution and medium ecological risk, and the site was generally at a slight-medium ecological risk level. The Sb concentration of Zijiang river was relatively high, with an average of 10.51μg/L. Sb mainly came from the antimony mining industry in the upper and middle reaches, and was controlled by human activities such as high antimony concentration surface water irrigation, landfills and coal burning; Cd mainly came from human activities such as pesticides, fertilizers, household garbage and urban wastewater; Cr was mainly derived from soil parent material, while Cu, Zn, As, Ni, Pb were controlled by soil parent material and human activities.